50 years of disseminating historical knowledge: The Revista de Historia - Sandí Morales, José Aurelio (2025)
As part of the celebrations for the fiftieth anniversary of the School of History at the National University of Costa Rica (UNA), the 50th anniversary of its History Journal is also being commemorated. The journal has established itself as one of the most important publications on historical knowledge in Central America. With 92 issues, the journal has reflected regional historiographical change and has transcended borders, publishing articles on various countries in the Americas, from Uruguay to the United States, becoming an essential and accessible source thanks to the digitisation of its collection. It is a crucial reference point for Costa Rican historiography, serving as a launching pad for multiple generations of established and emerging historians, and to a certain extent, it was a meeting point between the history schools of the UNA and the UCR between 1986 and 2012. To commemorate its half-century of existence, a special dossier was produced with articles by UNA professors and academics exploring a variety of topics, from institutional experiences (Rodrigo Quesada, José Daniel Gil) to in-depth research on Central American scientific unionism (Margarita Silva), the socio-natural relationship on multiple scales (Mario Samper), the history of justice (Amando Torres), and secularisation in Costa Rica (José Aurelio Sandí), reaffirming the role of the journal as an essential bastion for the dissemination and innovation of historical knowledge.